Assessment of Knowledge about Halitosis and its Management Amongst Fresh Medical Graduates in Lahore, A Survey - Rija Asghar, Aiman Malik, Muhammad Shairaz Sadiq, Fareed Ahmed, Mehek Javed, Bersha Mir, Zaid Bin Sohail, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The origin of halitosis comes from the Latin word "Halitus" meaning 'breath, exhaled air.' Halitosis is an unpleasant odour exhaled in breathing, also known by the name of bad breath. The purpose of this research is to evaluate the level of knowledge of fresh medical graduates and their management skills towards halitosis. Methods & Materials: A questionnaire was designed to collect the required information from the fresh medical graduates. The duration of the study was 6 months January 2020 to June 2020. Study was conducted on fresh medical graduates from private and public sector across Lahore visiting the dental Outpatient Department of Institute of Dentistry, CMH Lahore Medical College Results: The study sample comprised of 59.3% females and 40.7% of males. Astonishing, 71.4% did not treat halitosis amongst patients visiting for treatment whilst 28.6% provided treatment for halitosis. Surprisingly, only 28.6% of medical doctors treated oral malodour. Alarmingly 71% doctor did not treat oral malodour. A whopping 95.2 % blamed poor oral hygiene to the biggest cause of halitosis. Stagnation of food secured 2nd place with 70% followed by chronic periodontal disease at 64.8%. Surprisingly, 0.4% mentioned that eating Garlic/raw food was considered as a least reason for oral malodour. Discussion: Conclusion: Halitosis was prevalent among patients visiting medical doctors for treatment. They can benefit from enhanced understanding and encouragement to improve their own and the patient's oral hygiene because of their responsibilities to diagnose and improve oral health..